Improving Ninth Graders' Mastery Of Simple Past Tense Through Word Arrangement Games - Dinda Nurlaini; Candraning Prihatini; Ahmad Syafiq (Journal of English Education, Literature and Linguistics, 2025)
This Classroom Action Research aims to improve the mastery of Simple Past Tense material for 9th-grade students through the application of the Word Arrangement game at MTs Jabal An-Nur Al Islami. This research involved 16 students and was conducted in two cycles consisting of planning, action, observation, and reflection stages. Data was collected through pre-tests, post-tests, and observation. The research results show a significant improvement in students' grammar mastery. The average score increased from 38.13% on the pre-test to 57.5% in the first cycle, and reached 86.25% in the second cycle. The Word Arrangement game creates an interactive and fun learning environment, increases student motivation, and strengthens their understanding of regular and irregular verb forms. This strategy also reflects the principles of constructivist theory, which encourages collaboration, active participation, and contextual learning without relying on digital tools. This finding indicates that simple game-based learning strategies are highly effective in teaching grammar, particularly in educational environments with limited facilities.